Kontekstualisasi Basa Dayak Ngaju dalam Liturgi Gereja Kalimantan Evangelis (GKE) di Jemaat Eben Ezer Banjarmasin - Tahan cambah; Agunius Gosyen (Jurnal Teologi Pambelum, 2023)
In the early history of the Kalimantan Evangelical Church (GKE), the Dayak Ngaju language has become an effective medium for conveying the gospel in Kalimantan. Special research on the contextualization of the Dayak Ngaju language has not been carried out in much depth. This paper aims to reveal the contextualization process of the Dayak Ngaju language used in GKE liturgies, especially the Eben Ezer Congregation. The method used is qualitative, using J. D. Crichton's and Lawrence a. Hoffmann framework for understanding liturgical history combined with David Hesselgrave and Rommen's understanding of the contextualization process and James F. White's thoughts on liturgical contextualization. In history, it was found that liturgical contextualization at GKE was influenced by the translation of the Bible into the Dayak Ngaju language (Surat Barasih), liturgical texts in the Dayak Ngaju language, Nyanyin Ungkup (Congregational Songs in the Dayak Ngaju language), and other spiritual coaching materials. The results of the study show that there is a reversal of the contextualization process of the Dayak Ngaju language in GKE. At first, it was relevant to the context, but over time, the context changed so that the contextualization of the Dayak Ngaju language at GKE Eben Ezer had to change too.